2019
DOI: 10.3390/geosciences9050207
|View full text |Cite
|
Sign up to set email alerts
|

Changing Impacts of North Atlantic Tropical Cyclones on Extreme Precipitation Distribution across the Mid-Atlantic United States

Abstract: Almost every year, north Atlantic tropical cyclones (TCs) are responsible for significant socioeconomic losses across the Mid-Atlantic USA. However, the extent to which TC activity contributes to the changes in the probability distributions of the extreme precipitation have not yet been comprehensively characterized for this region. In this study, a quantile regression method was used to investigate the trends of the lower (τ = 0.2) and upper (τ = 0.8) quantiles of annual and seasonal daily maximum precipitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…In addition to this, it was observed that seasonal modes of AMF dates have weakened over time for a number of sites along the coastal region with the emergence of significant modes during late spring and early summer (May-June) as well as fall season (mid-September-November). The reason for the emergence of seasonality modes during the month of November along the coastal sites might be due to an increase in the heavy precipitation trends associated with tropical cyclones in the North Atlantic basins over the last 30 years [26,[40][41][42][43]. Similarly, the emergence of modes during the months of May and early June might be due to the emergence of extreme precipitation seasonality modes during late spring and early summer season for the latest time period as shown by Dhakal et al [25].…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…In addition to this, it was observed that seasonal modes of AMF dates have weakened over time for a number of sites along the coastal region with the emergence of significant modes during late spring and early summer (May-June) as well as fall season (mid-September-November). The reason for the emergence of seasonality modes during the month of November along the coastal sites might be due to an increase in the heavy precipitation trends associated with tropical cyclones in the North Atlantic basins over the last 30 years [26,[40][41][42][43]. Similarly, the emergence of modes during the months of May and early June might be due to the emergence of extreme precipitation seasonality modes during late spring and early summer season for the latest time period as shown by Dhakal et al [25].…”
mentioning
confidence: 87%
“…More specifically, the goals of this study are to: (1) precisely explore whether the seasonality of AMF is multimodal for the NE and MW region; and (2) investigate whether there have been temporal shifts (non-stationarity) in the seasonality of the AMF across the region, and if yes, whether the temporal shifts have been caused by either weakening, strengthening, emergence or weathering of distributional modes of timing of AMF during different seasons. Results from this study can be helpful in disaster risk management [26] as well as in identifying changes in flood-generating mechanisms [23].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The probability distribution function of precipitation is expected to change under warmer climate (IPCC, ), and hence it is important to understand how the North Atlantic TCs impact the spatial distribution and temporal characteristics of extreme precipitation of the eastern United States. Previous studies lack explicit information related to temporal changes (strengthening or weakening) in the TC‐linked component of the annual and seasonal maximum rainfall series which have important implications on the sizing of flood protection infrastructure and, in general, flood risk management and preparedness (Dhakal, ). In this article, we studied the contribution of TCs to the variability and changes of daily extreme precipitation at 667 stations in the eastern United States for the period 1950–2011, with particular focus on changing spatiotemporal correlations of long‐term rainfall variability with TC activity measured by ACE index.…”
Section: Discussionmentioning
confidence: 99%
“…In these circumstances, it is reasonable to assume that the heavy rains are associated with the circulation of the tropical system (Kunkel et al, 2010). Several past studies have analysed TC-rainfall events utilizing a threshold of a 500-km radius of influence to link precipitation events with TCs (Rodgers et al, 2000(Rodgers et al, , 2001Douglas and Englehart, 2001;Larson et al, 2005;Lau et al, 2008;Jiang and Zipser, 2010;Kunkel et al, 2010;Barlow, 2011;Jiang et al, 2011;Nogueira et al, 2013;Prat and Nelson, 2013;Villarini et al, 2014;Wright et al, 2015;Aryal et al, 2018;Dhakal and Tharu, 2018;Dhakal, 2019).…”
Section: Identification Of Tc-precipitation In the Eastern United Statesmentioning
confidence: 99%